Cultural issues on accessing mental health services in Nepali and Iranian migrants communities in the UK. (21st July 2021) - Simkhada, Bibha; Vahdaninia, Mariam; van Teijlingen, Edwin; Blunt, Hannah
Abstract: Mental health in Black Asian and Minority Ethnic (BAME) communities is a rising public health concern in the UK, with key challenges around accessing mental health services. Our understanding of mental health issues in the growing Nepali and Iranian communities in the UK is very limited. Therefore, this study aims to explore the major factors affecting access to, and engagement with NHS mental health services. This study used a qualitative approach comprising in‐depth interviews with seven Nepali, eight Iranians and six community mental health workers in the south of England. The data were analysed using a thematic approach. Six themes were identified: (1) stigma and fear; (2) gender; (3) language; (4) tradition and culture; (5) family involvement; and (6) lack of cultural awareness in health workers, all appearing to be major issues. This study contributes to a shared understanding of mental illness within two given cultural contexts to promote early interventions in UK mental health services. Developing cross‐cultural perspectives in health care should be a priority in practice.